2012
DOI: 10.1007/s10530-012-0364-0
|View full text |Cite
|
Sign up to set email alerts
|

A risk assessment for managing non-native parasites

Abstract: The spread of non-native parasites with the movement of animals is a primary cause of disease emergence worldwide. Such introductions can threaten native biodiversity, hinder conservation efforts and limit the socio-economic development of natural resources. Evaluating the threats from alien parasites can represent a considerable challenge, due to the limited information that often accompanies their introduction. We present a comprehensive modular risk assessment scheme that supports the management of non-nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…Hockley et al 2011;Reading et al 2011). However, examples of serious disease outbreaks following the translocation of monogenean parasites, such as Gyrodactylus salaris (Bauer et al 2002;Bakke et al 2007), highlights the importance of continued monitoring and prompt risk assessment to inform management (Williams et al 2013). There was no evidence that parasite spillover had occurred in any of the studied fish communities in the introduced range, with no recordings of the introduced parasites in the sympatric native fishes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hockley et al 2011;Reading et al 2011). However, examples of serious disease outbreaks following the translocation of monogenean parasites, such as Gyrodactylus salaris (Bauer et al 2002;Bakke et al 2007), highlights the importance of continued monitoring and prompt risk assessment to inform management (Williams et al 2013). There was no evidence that parasite spillover had occurred in any of the studied fish communities in the introduced range, with no recordings of the introduced parasites in the sympatric native fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst fish introductions in England Wales are routinely screened for certain 'notifiable' diseases before release (at least where introduction is intentional and approved; Davies et al 2013), there is arguably a requirement for increased parasite screening for introductions of non-native fish. However, with differing legislative, economic and political drivers, managing the introduction and spread of non-native pathogens represents a complex global challenge (Williams et al 2013). Although we found few examples of non-native fish pathogens being imported directly on seven nonnative fishes, Phillips et al (2010) found that, whilst initially an invasive species may experience parasite release, those that do remain-even in low abundance-might re-establish, having consequences on both the non-native host and the wider fish community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spread of parasites is a major source of disease emergence for vertebrate taxa, including humans (George 2008, Mack et al 2000, Williams et al 2013). Climate change and anthropogenic landscape alterations, such as fragmentation and suburban sprawl, have been linked to tick range expansions worldwide, resulting in changes to tick community structure and altered tick-borne pathogen dynamics (Childs and Paddock 2003, Cumming and Van Vuuren 2006, Gage et al 2008, George 2008, Léger et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Quiroz-Martínez and Salgado-Maldonado, 2013;Scholz and Choudhury, 2014). That said, future monitoring programmes still need to take into account parasite protocols in order to improve the knowledge about distribution, disease threats, epidemiology and spatiotemporal variation of non-native parasites in nature (Williams et al, 2013). Additionally, other management actions can be pursued to diminish the effects of non-native parasites such as eradication and control programmes of either hosts or pathogens (e.g.…”
Section: Discussionmentioning
confidence: 99%